Effect of Ultrasonication Extraction Time on Determination of Flavonoid Levels in Ciplukan Plants (Jurnal Bahan Alam Terbarukan, 2022)
Ciplukan contains bioactive substances in the form of flavonoids, saponins, alkaloids, polyphenols, vitamin C, stearic acid, palmitic acid. Bioactive substances from natural ingredients are known to function as immunomodulators that can increase the body's immune system, activate the body's natural defenses and restore immune system imbalances. Immunomodulators are important in studies related to the issue of the coronavirus disease 19 (Covid-19) pandemic. The purpose of this study was to determine the effect of the extraction time on the ultrasonic method on the flavonoid yield of ciplukan plants using methanol as a solvent. The method used is ultrasonication extraction with a variable extraction time. The analysis was carried out by qualitative analysis using a solution of qursetin to determine the concentration of flavonoids. The results of the study obtained the optimum flavonoid concentration at the extraction time of 15 minutes